2023
DOI: 10.3390/nu15102412
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Life’s Simple 7, Psychosocial Health, and Physical Frailty, Hospital Frailty, and Comprehensive Frailty 10 Years Later

Abstract: This study aims to examine the associations between midlife Life’s Simple 7 (LS7) status, psychosocial health (social isolation and loneliness), and late-life multidimensional frailty indicators, and to investigate their synergistic effect on frailty. We used cohort data from the UK Biobank. Frailty was assessed using physical frailty phenotype, hospital frailty risk score, and frailty index. Cox proportional-hazards models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the prognosis of stroke patients is poor compared with that of individuals with other diseases (Droś et al, 2023), and the recurrence of stroke easily leads to anxiety, depression, and other negative emotions, which aggravate the risk of multidimensional frailty. Notably, this study showed that the prevalence of multidimensional frailty in middle-aged stroke patients was 44.5%, which was higher than that of the general population (Wang et al, 2023). Frailty does not exist in older people only (Loecker et al, 2021), suggesting the need to focus also on the development of frailty in younger stroke patients.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, the prognosis of stroke patients is poor compared with that of individuals with other diseases (Droś et al, 2023), and the recurrence of stroke easily leads to anxiety, depression, and other negative emotions, which aggravate the risk of multidimensional frailty. Notably, this study showed that the prevalence of multidimensional frailty in middle-aged stroke patients was 44.5%, which was higher than that of the general population (Wang et al, 2023). Frailty does not exist in older people only (Loecker et al, 2021), suggesting the need to focus also on the development of frailty in younger stroke patients.…”
Section: Discussionmentioning
confidence: 66%